THE IMPORTANCE OF ANIMALS IN ENVIRONMENTAL PROTECTION AND IN THE FUNCTIONING OF NATURAL SYSTEMS (Academicia Globe: Inderscience Research, 2022)
This article discusses animals that are not only part of natural systems, but also have great economic and economic importance. Wild animals and the results of their activities are used in various sectors of the economy.